Isolation and Purification of L-Asparaginase from Persian Gulf Streptomyces Isolates and Evaluation of It’s Cloned Gene Expression in Escherichia Coli by Real-Time and SDS-PAGE - Hadiseh Soofer; Kumarss Amini; Seyed Mohammad Masoud Shushtarian (Journal of Advanced Biomedical Sciences, 2020)
Background & Objective: Asparaginase enzymes are effective in treating lymphoblastic leukemia cancer. This enzyme is isolated from bacterial sources and commercially available as an anticancer drug. The aim of this study was to isolate and purifiy L-asparaginase from persian gulf Streptomyces isolates and evaluate its cloned gene expression in E. coli by Real-Time and SDS-PAGE. Materials & methods: Streptomyces isolates were isolated from the Persian Gulf and identified by biochemical tests, then, L-asparaginase genes were isolated from streptomyces by PCR method. The amplified fragment was entered into vector pTG19 by the TA cloning technique. In the next step, the recombinant vector was transformed into E. coli using CaCl2 method and cloning confirmation using conventional methods. Result: The results of this study showed that Streptomyces isolates from the Persian Gulf were capable of producing L-asparaginase. Eventually, the gene of this enzyme was successfully transformed to E. coli by vector and produced high efficiency L-asparaginase. Conclusion: Finding new bacterial strains producing L-asparaginase and using gene engineering techniques can lead to better performance of these enzymes, thereby taking a big step in the direction of increasing and facilitating the production of L-asparaginase in the pharmaceutical industry.